Investigation of interface deformation dynamics during high-Weber number cylindrical droplet breakup. (November 2020) - Kaiser, J.W.J.; Winter, J.M.; Adami, S.; Adams, N.A.
Highlights: High resolution simulations of aerodynamic fragmentation. Observation of hat formation on the upstream side of the droplet. Hat formation associated with early-stage interface disturbances. Skewness enables characterization of breakup stages. Local recirculation zones associated with interface shearing. Abstract: In this work, we study the interface deformation during the early-stages of breakup of a water column in an ambient flow field by high-resolution numerical simulation. The compressible Navier–Stokes equations govern the motion of the two fluids, and capillary forces and viscous effects are considered. We model the multiphase flow with a level-set based sharp-interface method with conservative interface interaction. The governing equations are discretized with a finite-volume approach with low-dissipation flux reconstruction at cell faces based on a fifth-order WENO scheme, and a third-order Runge–Kutta TVD explicit time integration scheme. We validate our numerical simulations by comparison with experimental reference data. We achieve an accurate prediction of wave dynamics and interface deformation of the liquid column. Both flattening of the cylinder (first stage) and shearing of the sheet at the droplet equator (second stage) are reproduced. We show that a distinct pressure-wave pattern forms in the supersonic flow region near the cylinder equator after shock passage. These waves interact with the phase interface, resulting in local interface disturbances that coincide with the onset of the second stage. Resolving these waves is essential for the prediction of the hat-like structure at the upstream face of the cylinder during the second stage of the breakup, which so far only has been observed in experimental visualizations of this particular breakup mode. Our results support the connection of the sheet-stripping mechanism with the local formation of recirculation zones. Extending previous work, our high-resolution results indicate that recirculation zones appear at multiple locations along the interface, and are directly linked to the growth of water sheet-forming interface disturbances.